Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/tox.23330
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin functions as an anti‐inflammatory and antioxidant agent on arsenic‐induced hepatic and kidney injury by inhibiting MAPKs/NF‐κB and activating Nrf2 pathways

Abstract: Chronic arsenic exposure has been associated with various toxic effects, especially to the organs of liver and kidney. As a plant polyphenol, curcumin is the most vital bioactive ingredient of turmeric and has a wide range of pharmacological activities. In the present study, we investigated the potential roles of curcumin against arsenic‐induced liver and kidney dysfunctions in mice. Curcumin treatment (200 mg/kg) not only decreased the deposition of arsenic in liver and kidney, but also relieved the hepatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In addition, as a natural plant antioxidant, curcumin potently activated Nrf2 to prevent hepatorenal injury induced by arsenic overdose and dimethylnitrosamine toxicity [ 18 , 59 ]. Similar to our results, we found that the administration of AFB1 and curcumin promoted the expression of Nrf2 and its downstream genes that were inhibited by AFB1 in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a natural plant antioxidant, curcumin potently activated Nrf2 to prevent hepatorenal injury induced by arsenic overdose and dimethylnitrosamine toxicity [ 18 , 59 ]. Similar to our results, we found that the administration of AFB1 and curcumin promoted the expression of Nrf2 and its downstream genes that were inhibited by AFB1 in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a phenolic pigment extracted from the rhizome of Curcuma longa (turmeric) [ 14 ], which has been proven to exhibit multiple biological activities encompassing antioxidant, antibacterial, anti-inflammatory, and immune-enhancing properties in various experiments [ 15 , 16 ]. There is evidence that curcumin offers protective potential against tissue injury caused by certain drugs and environmental toxins: curcumin could prevent carbon tetrachloride (CCL4)-induced acute liver damage via inhibition of oxidative stress and inflammation [ 17 ]; curcumin can alleviate arsenic-induced hepatorenal toxicity by activating Nrf2 and inhibiting the MAPK–NF-κB pathway [ 18 ]; curcumin has also been found to exert cytoprotective and antioxidant effects against OTA-induced toxicity in rats [ 19 ]. These studies present evidence in support of the use of curcumin as a protective antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…As we known, curcumin is classical anti-oxidative and anti-inflammatory agent which was widely used in the treatment of many inflammatory and degenerative diseases [ 43 , 44 ]. Previous studies showed that curcumin exerts chondro-protective effects by regulating oxidative stress [ 45 ], endoplasmic reticulum stress [ 30 ], inflammation [ 46 ], autophagy [ 47 ] in different OA models.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, 6 weeks supplementation with 500 mg resveratrol can alleviate UC in patients associated with reduction in plasma levels of TNF-α and activity of NF-κB in peripheral blood mononuclear cells (PBMC) [176]. Curcumin, a natural active component extracted from the root of turmeric, a rhizomatous herbaceous perennial plant of the ginger family, is widely known to possess antiinflammatory and antioxidant effects [88]. Previously, numerous studies in both animals and cell lines have demonstrated the inhibitory activity of curcumin on TLR4/MyD88/NF-κB signaling [89,90,177,178].…”
Section: Stilbenes Resveratrolmentioning
confidence: 99%